Service user and family member perspectives on services for mental health, substance use/addiction, and violence: a qualitative study of their goals, experiences and recommendations. Issue 1 (December 2016) - Haskell, Rebecca; Graham, Kathryn; Bernards, Sharon; Flynn, Andrea; Wells, Samantha
Abstract Background Mental health and substance use disorders (MSD) are significant public health concerns that often co-occur with violence. To improve services that address MSD and violence [MSD(V)], it is critical to understand the perspectives of those most affected, people who have sought help for MSD(V) (i.e., "service users"), especially those with co-occurring issues, as well as their family members. Methods We conducted structured interviews with 73 service users and 41 family members of service users in two Ontario communities (one urban, one rural) regarding their goals related to help-seeking, positive and negative experiences, and recommendations for improving systems of care. Results Overall, participants expressed a need for services that: (1) are respectful, nonjudgmental, and supportive, help service users to feel more 'normal' and include education to reduce stigma; (2) are accessible, varied and publicly funded, thereby meeting individual needs and addressing equity concerns at a systems level; and (3) are coordinated, holistic and inclusive of family members who often support service users. Conclusions The findings provide a rich understanding of how service users and their families perceive services for MSD(V) issues and identify key ways to better meet their needs.